THE LEARNING EXPERIENCE OF GREATER CHINESE STUDENTS IN FRENCH UNIVERSITIES: A CROSS-CULTURAL PERSPECTIVE - Hsin-I Lee; Kemo Badiane; Yiru Xu (Faculty of Languages and Arts, Universitas Negeri Yogyakarta, 2019)
Today, more and more Greater Chinese students are motivated to study in Western universities more specifically French universities. This makes France one of the fourth most popular destination for international students. Using pragmatics and social-cultural constructivist perspectives, this article aims at improving the adaptation of the Greater Chinese students benefiting from a French-Greater Chinese university exchange. The method employed in this study was descriptive qualitative research based on interviews and online surveys with Greater Chinese students for two academic years before they went to France and while staying there. The results at the end of which we made some suggestions for academic purposes took place prior to these exchanges. Furthermore, we focus on what seems the most important to us, meaning adaptation to French university pedagogical methods. Thus, the article proposed a presentation of the characteristics, the main obstacles faced and the appropriate advice for the elaboration of the syllabus. To summarize, the paper proposes reflections in the sense of designing FFL preparatory syllabi specific to study programs. By listing the real encountered problems and suggesting means to overcome them, we think this can be helpful to FFL teachers and students involved. Implications for teachers, researchers and learners are highlighted. Keywords: FFL, academic competences, university pedagogical methods, lectures, FSP (French for Specific Purposes)